'Her Majesty the Baby': narcissistic states in babies and young children*. Issue 2 (4th May 2017) - Hurley, Anne
Abstract : This article considers narcissistic states in babies and young children with some reference to the myth of Narcissus in Ovid's Metamorphosis. The object-seeking character of babies from the beginning of life is elaborated in connection with selected research from mother–baby interaction. This forms the backdrop to a discussion of withdrawal into illusions of self-sufficiency and denial of dependence in adverse circumstances. Two clinical cases are discussed in some depth. One boy whose superiority, self-reliance and pseudo maturity is prompted by anxieties around separation as he approaches starting school is considered within the parameters of ordinary transient narcissism. The lengthy psychotherapy of another child, who developed entrenched narcissistic defences as a response to traumatic, abusive and neglectful experiences in early life, and who needed considerable help, is described in greater detail. Some links are made with difficulties associated with the emergence from narcissistic functioning and encountering the pain of separation and loss.